The development of partnership based structure in comparison to the concept of musharakah (sharikah) with special reference to Malaysia - Abd Ghadas, Zuhairah Ariff; Engku Ali, Engku Rabiah Adawiah (International Islamic University Malaysia, 2011)
In Malaysia, most of the businesses are micro, small and medium. According to the SME Annual Report 2010/2011, the latest statistics indicate that SMEs constitute 99.2% of the total business establishments and contribute about 32% of GDP and 59% of total employment. In carrying out the SMEs, the option of business vehicles which are available in Malaysia is only the conventional business structure, namely, sole proprietorships, partnerships and company. For the micro, small and medium businesses, the company structure is observed not to be appropriate due to its formal and highly regulated business structure. As such, most of the SMEs are carried out in the form of sole proprietorships and partnerships. This can be seen from the statistics published by Companies Commission of Malaysia which provides that there are 4,660,067 sole proprietorships and partnerships registered compared to only 970,396 of companies being registered. The tax scheme is also another discouraging factor which makes the partnership as a better option for SMEs. In certain sectors, particularly the professionals, for example, lawyers and accountants, the business can only be carried out in the form of sole proprietorships or partnerships. This article intends to highlight the development of partnership based structure in Malaysia and compare it with Islamic version of partnerships structure (Sharikah).